Thronebreakers - Coffindaffer, Rebecca (Coffindaffer, Rebecca. Crownchasers, 2021)
"Alyssa Farshot never wanted to rule the empire. But to honor her uncle's dying wish, she participated in the crownchase, a race across the empire's 1,001 planets to find the royal seal and win the throne. Alyssa tried to help her friend, Coy, win the crownchase, but just as victory was within their grasp, Edgar Voles killed Coy--and claimed the seal for himself. Broken-hearted over her friend's death, Alyssa is hell-bent on revenge. But Edgar is well protected in the kingship. Alyssa will have to rally rivals, friends, and foes from across the empire to take him down and change the course of the galaxy"--Amazon.